OPPORTUNITIES FOR FORMING ENVIRONMENTAL AND ETHICAL COMPETENCE OF STUDENTS (Scientific journal of the Fergana State University, 2023)
This article presents the foreign experience and national educational opportunities for the formation of environmental moral competence of students, social and pedagogical tasks associated with the development of their environmental moral responsibility and respect for nature, the issues of educating environmental activity and responsibility.